A prospective, randomized, single blind study comparing polyglactin-910 fast suture and chromic catgut suture in episiotomy repair - Tanya; N. K., Roopa; N., Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Episiotomy is a standard surgical procedure performed during childbirth to enlarge the vaginal opening and facilitate baby delivery. Effective suturing techniques promote optimal wound healing, minimize complications, and enhance postpartum recovery for women undergoing episiotomy repair. This study aims to compare the effect of two different suture materials- chromic catgut and fast absorbable polyglactin-910 in the repair of episiotomy and its complications. Methods: A prospective, randomized, single blinded study was conducted at the department of obstetrics and gynecology, in a tertiary care hospital in India, between April 2021 and September 2022. Women aged 18-35 years with a singleton pregnancy undergoing vaginal delivery with episiotomy were included after giving informed written consent and fulfilling inclusion and exclusion criteria. Either chromic catgut (n=58) or polyglactin-910 fast (n=58) suture was used in episiotomy repair. The primary endpoint was to assess perineal pain following episiotomy repair using (VAS) visual analogue scale. The secondary endpoints were to assess wound healing using the REEDA scale, short term complications (hematoma, swelling, puerperal fever, dehiscence, wound healing and re-suturing), long term complications (feeling of slight stitches, dyspareunia and suture granuloma), intraoperative suture parameters, and any adverse events were noted. Results: Perineal pain, analgesic requirement, a feeling of slight stitches, and swelling were significantly more in the chromic catgut suture group compared to the polyglactin-910 fast absorbable suture group. Conclusions: The study concluded that polyglactin-910 fast absorbable suture is superior to chromic catgut suture and recommended its use over chromic catgut suture.